2012
DOI: 10.1038/ncomms2240
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection by Klotho through downregulation of TRPC6 channels in the mouse heart

Abstract: Klotho is a membrane protein predominantly produced in the kidney that exerts some anti-ageing effects. Ageing is associated with an increased risk of heart failure; whether Klotho is cardioprotective is unknown. Here we show that Klotho-deficient mice have no baseline cardiac abnormalities but develop exaggerated pathological cardiac hypertrophy and remodeling in response to stress. Cardioprotection by Klotho in normal mice is mediated by downregulation of TRPC6 channels in the heart. We demonstrate that dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
307
3
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 294 publications
(329 citation statements)
references
References 57 publications
(104 reference statements)
9
307
3
5
Order By: Relevance
“…32 Moreover, cardioprotection of Klotho was proposed to act through suppression of the TRPC6 signal pathway. 31 Klotho mRNA was found in the sinoatrial node, 32 but membrane Klotho protein has never been shown to be expressed in cardiomyocytes or cardiac fibroblasts. We are primarily examining a different aspect of Klotho biology, which is the systemic effects of soluble Klotho.…”
Section: Discussionmentioning
confidence: 99%
“…32 Moreover, cardioprotection of Klotho was proposed to act through suppression of the TRPC6 signal pathway. 31 Klotho mRNA was found in the sinoatrial node, 32 but membrane Klotho protein has never been shown to be expressed in cardiomyocytes or cardiac fibroblasts. We are primarily examining a different aspect of Klotho biology, which is the systemic effects of soluble Klotho.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms by which FGF‐23 could lead to adverse cardiovascular consequences include calcitriol deficiency, altered phosphorus homeostasis, systemic inflammation and oxidative stress, and sodium retention 31, 32, 33. Additionally, FGF‐23 may downregulate soluble α‐klotho,34 an enzyme with anti‐aging effects that was shown to protect the heart against cardiac hypertrophy and cardiac remodeling 35, 36. In a study by Reindl et al, FGF‐23 was significantly higher in patients who developed LV remodeling post ST‐segment–elevation myocardial infarction even after adjustment for biomarkers of myocardial necrosis, myocardial stress, and inflammation 37.…”
Section: Discussionmentioning
confidence: 99%
“…The recent report by Faul and coworkers (Faul et al, 2011) suggested that FGF23 may induce left ventricular hypertrophy by a direct, Klotho-independent action on cardiomyocytes. In contrast, Xie and coworkers (Xie et al, 2012) reported that Klotho may be cardioprotective by an FGF23-independent downregulation of stressinduced calcium channels.…”
Section: Introductionmentioning
confidence: 91%